Urbanism for people: Innovative public responses to urban conflicts in Santiago, Chile - Pablo Fuentes Flores (Materia Arquitectura)
State actions on Chilean cities are characterized for addressing large scale issues such as traffic congestion, air pollution, and socio-residential segregation. Nonetheless, in recent years the State has also participated in initiatives that face small scale but highly significant issues. This kind of public action will be understood as urban planning for people, a definition coined by Danish planner Jan Gehl (2006), author of a methodology that studies in detail people´s behavior in public spaces. The aim of this paper is to describe four interventions in which the State has directly or indirectly participated, to identify the conflicts involved and the achievements accomplished or errors made during the implementation to obtain hints aimed to the creation or improvement of new territorial planning politics. The article concludes that in order to transform the public space of Chilean cities it is necessary to implement a new model of urban governance that allows cross-sector coordination and implementation, with effective community participation and public servants prepared in projects' management, effective communication and team work.